Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/00051144.2017.1372124
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting hybrid time switching-based and power splitting-based relaying protocol in wireless powered communication networks with outdated channel state information

Abstract: Wireless powered communication networks (WPCNs) have attracted much research interest in fifth generation (5G) wireless networks. With the help of WPCN, the reliability and battery life of wireless low-power devices can be enhanced. In this paper, we investigate throughput and ergodic capacity in WPCN-assisted amplify-and-forward relaying systems considering two transmission modes, including delay-tolerant and delay-limited. More importantly, we propose energy harvesting protocol so-called hybrid time switchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…wave, solar, wind, etc.) can be collected to transform into electricity [1][2][3][4][5][6][7]. In particular, the authors in [8] proposed two relaying protocols so-called time switching-based relaying (TSR) protocol and power splittingbased relaying (PSR) protocol to enable EH and information processing at the relay node.…”
Section: Introductionmentioning
confidence: 99%
“…wave, solar, wind, etc.) can be collected to transform into electricity [1][2][3][4][5][6][7]. In particular, the authors in [8] proposed two relaying protocols so-called time switching-based relaying (TSR) protocol and power splittingbased relaying (PSR) protocol to enable EH and information processing at the relay node.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1 demonstrates a relay-aided CR-NOMA network having a primary source P S and several intermediate relays {R k |k = 1, 2, ..., K} employing relaying protocols [31], [32], [33], i.e. DF scheme.…”
Section: System Model Figurementioning
confidence: 99%
“…To overcome the problem of less performance, a new technique namely repeated relay selection is proposed that is based on updated CSI. It is shown that the throughput of updated CSI is much better as compared to outdated CSI .…”
Section: Relay Selection Techniquesmentioning
confidence: 99%